A bridged low band gap A–D–A quaterthiophene as efficient donor for organic solar cells. Issue 2 (20th November 2014) - Baert, François; Cabanetos, Clément; Leliège, Antoine; Kirchner, Eva; Segut, Olivier; Alévêque, Olivier; Allain, Magali; Seo, Gijun; Jung, Sungyeop; Tondelier, Denis; Geffroy, Bernard; Roncali, Jean; et al.
Abstract : Covalent bridging of the central 2, 2′-bithiophene of α, ω-bis(dicyanovinyl)quaterthiophene derivatives leads to a reduced band gap and efficient organic solar cells. Abstract : α, ω-Bis(dicyanovinyl)quaterthiophene1 with a median 4, 4-diethyl-4 H -cyclopenta[2, 1- b :3, 4- b ′]dithiophene has been synthesized. UV-Vis absorption data show that the covalent bridging of the inner 2, 2′-bithiophene leads to a significant reduction of the HOMO–LUMO gap essentially due to an increase of the HOMO level as confirmed by electrochemical and theoretical results. X-ray diffraction analysis of a single crystal of1 shows that except for the out-of-plane ethyl groups, the conjugated system displays a quasi-planar geometry while the molecular packing exhibits strong π-stacking interactions and multiple short intermolecular contacts. Quaterthiophene1 has been used as active donor material in organic solar cells of various architectures including bi-layer planar hetero-junctions and hybrid co-evaporated bulk hetero-junctions with C60 as electron acceptor material. A maximum conversion efficiency of 4.30% is obtained with a hybrid co-evaporated device. These results are discussed in terms of structure–properties relationships with reference to the open-chain parent α, ω-bis(dicyanovinyl)quaterthiophene2 .